2013
DOI: 10.1093/gerona/glt187
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Replacement Therapy Prevents Sarcopenia by a Dual Mechanism: Improvement of Protein Balance and of Antioxidant Defenses

Abstract: The aim of our study was to elucidate the role of growth hormone (GH) replacement therapy in three of the main mechanisms involved in sarcopenia: alterations in mitochondrial biogenesis, increase in oxidative stress, and alterations in protein balance. We used young and old Wistar rats that received either placebo or low doses of GH to reach normal insulin-like growth factor-1 values observed in the young group. We found an increase in lean body mass and plasma and hepatic insulin-like growth factor-1 levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 63 publications
4
52
0
1
Order By: Relevance
“…GH replacement therapy is known to act as an antioxidant because it upregulates the expression of important intracellular antioxidant enzymes, such as catalase, glutathione peroxidase, and glucose-6-phosphate dehydrogenase [28]. It has been shown that IGF-1 reduces oxidative Correlation of d-ROMs with RHI in GHD stress and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…GH replacement therapy is known to act as an antioxidant because it upregulates the expression of important intracellular antioxidant enzymes, such as catalase, glutathione peroxidase, and glucose-6-phosphate dehydrogenase [28]. It has been shown that IGF-1 reduces oxidative Correlation of d-ROMs with RHI in GHD stress and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the levels of growth hormone (GH) and their relevant regulators (Insulinlike Growth Factor-IGF family) are usually lower in the elderly subjects, and these situation could further explain skeletal muscle mass wasting. In a recent in vivo study, Briosche et al (45) proved that GH supplementation in old mice determined an increase in lean body mass, with an elevated synthesis rate of skeletal muscle protein and mitochondrial biogenesis pathways. Moreover, they registered a lowering of age-associated oxidative damage, an increase of plasma and hepatic IGF-1 levels, and an induction of antioxidant enzymes in the skeletal muscle of the treated animals.…”
Section: Other Mechanism Involved In Sarcopeniamentioning
confidence: 99%
“…Multiple strategies have been proposed to reduce muscle loss, including exercise training (Montero-Fernandez & Serra-Rexach, 2013), nutritional supplements (Karelis, Messier, Suppere, Briand, & Rabasa-Lhoret, 2015;Malafarina, Uriz-Otano, Iniesta, & GilGuerrero, 2013), and hormone replacement (Brioche et al, 2013). Among these, nutritional supplementation is considered an efficient and a safe method.…”
Section: Introductionmentioning
confidence: 99%